The Effect of Foot Massage with Lavender Essential Oil on The Sleep Quality of The Elderly in Banjar Gelumpang, Sukawati Village - Puspawati, Ni Luh Putu Dewi; Ari Santi, Ni Kadek; Saraswati, Ni Luh Gede Intan (Future Science, 2021)
Aging process in the elderly will cause health problems such as immobilization, incontinence, depression, malnutrition, decreased immune system, and sleep quality disorders. The puspose of this study was to determine the effect of foot massage with lavender essential oil on the sleep quality of the elderly. This research design used a pre-experimental with one group pre-test post-test design without a control group. The number of samples used was 20 respondents selected by purposive sampling and data collection using the pitsburgh sleep quality index questionnaire with the test result analyzed with Wilcoxon Sign Rank Test. The result showed that in pretest all respondents experienced poor sleep quality, and posttest data obtained that 13 respondents (65%) experienced good sleep quality. The results of data analysis using the Wilcoxon Sign rank test showed that the p-value = 0,000 <a (0,05) which means that there is an effect of foot massage with lavender essential oil on the sleep quality of the elderly in Banjar Gelumpang Sukawati village. Emphasis on certain points and the aroma of lavender will make the elderly feel relaxed so that the quality of sleep improved. It is suggests that the elderly and families to perform foot massage.